2018
DOI: 10.3389/fphys.2018.00496
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and Time-Dependent Expression of Cyclins, Cyclin-Dependant Kinases, and Apoptotic Genes in the Rumen Epithelia of Butyrate-Infused Goats

Abstract: In our previous study, we demonstrated that butyrate induced ruminal epithelial growth through cyclin D1 upregulation. Here, we investigated the influence of butyrate on the expression of genes associated with cell cycle and apoptosis in rumen epithelium. Goats (n = 24) were given an intra ruminal infusion of sodium butyrate at 0.3 (group B, n = 12) or 0 (group A, n = 12) g/kg of body weight (BW) per day before morning feeding for 28 days and were slaughtered (4 goat/group) at 5,7 and 9 h after butyrate infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Additionally, in the HC group of dairy cows, both the mRNA and protein expression of Bax was significantly increased, while Bcl-2 mRNA and protein expression were significantly decreased. The Bcl-2 to Bax ratio is mostly used to reveal the anti-apoptotic ability of cells [43]. Based on our findings, we confirmed that nourishing the dairy cows with an HC diet for up to 20 weeks can efficiently incite SARA by decreasing the rumen pH for up to 3 hours/day, which eventually increases the iE-DAP concentration that, on translocation, prompts mammary epithelial cell apoptosis by activating the NOD1/Caspase-8 pathway.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, in the HC group of dairy cows, both the mRNA and protein expression of Bax was significantly increased, while Bcl-2 mRNA and protein expression were significantly decreased. The Bcl-2 to Bax ratio is mostly used to reveal the anti-apoptotic ability of cells [43]. Based on our findings, we confirmed that nourishing the dairy cows with an HC diet for up to 20 weeks can efficiently incite SARA by decreasing the rumen pH for up to 3 hours/day, which eventually increases the iE-DAP concentration that, on translocation, prompts mammary epithelial cell apoptosis by activating the NOD1/Caspase-8 pathway.…”
Section: Discussionsupporting
confidence: 77%
“…The cell cycle of a mammalian cell is a complex process consisting of four phases including G1, G2, S, and M (Goodlad, ; Soomro et al, ). The cell cycle phases are strictly regulated by cyclins and cyclin‐dependent kinases (CDK) proteins (Matsushime et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This was similar as the results from Jamila Soomro et al . that that CyclinD1 combined with CDK2 activated G0 phase, which promoted cell proliferation (Soomro et al, ). In the other aspect, cyclin B is required prior to mitosis (G2/M‐phase) (Petersen et al, ; Coverley et al, ), which binds with CDK1 to accomplish cell division (Riabowol et al, ), explaining the activating of G2/M‐phase in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Physical stimulation by feed could increase rumen weight and muscle development [14], but volatile fatty acids are necassary for papilla development [15]. Soomro et al [16] reported that feeding butyrate at 0.3/kg BW significantly increased the length and thickness of the rumen papilla, and Zhang et al [17] reported that feeding 5% calcium salt propionic acid significantly increased papilla length and mRNA expression of GPR41, GPR43, and CCND1. For the simultaneous development of the rumen size (volume and muscle) and papilla, it is necessary to feed the calf with an appropriate proportion of concentrate and hay.…”
Section: Discussionmentioning
confidence: 99%